Proposal of a Measurement Scale of Decision Quality in Infrastructure Projects in Oil and Gas Exploitation - Gerardo Palacios Leyva; Juan Carlos Perez Garcia (European Scientific Journal, ESJ, 2018)
The objective in this paper is to present a proposal of a scale to measure the decision quality in infrastructure projects in the exploitation of oil and gas, as well as its foundations. One of the most important distinctions of Decision Analysis is the differentiation between a good decision and a good outcome, which is the approach of the scale, which occurs when decision making faces uncertainty. Therefore, a good decision does not always produce a good outcome. From this distinction, a progressive scale was designed, using an adjustment of the pairwise comparisons based on the Saaty scale achieving a quantitative hierarchy, which shows whether the decision guarantees quality, does not guarantee quality or is not acceptable. For its application, other existing decision processes used in the petroleum industry were located, from their common components a standardized decision analysis process was created, the common components are appropriate frame, objectives, decision and alternatives, risk and uncertainty, possibilities and modelling, values and exchanges and implementation and each of them subdivided into key aspects that are object of the measurement and evaluation. The objective set in a first stage was the proposed model of the measurement scale of decision quality and is subject to future validation work to verify its applicability in real life in a second stage.